Toward Types of Students’ Conceptions About Photons: Results of an Interview Study - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Teacher Education, 2022)
We report an exploratory interview study into students’ conceptions of photons developed by learners introduced to a QED model of photons as part of an introductory course in quantum physics at the secondary school level. By combining qualitative and quantitative research methods, we extract types of students’ imaginations about photons. Furthermore, we show that teaching a QED model of the photon might help to circumvent known (naive) particle notions of the photo